2023
DOI: 10.1186/s13054-022-04299-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in mortality and provision of intensive care in younger women and men with acute myocardial infarction or stroke

Abstract: Background Timely management of acute myocardial infarction (AMI) and acute stroke has undergone impressive progress during the last decade. However, it is currently unknown whether both sexes have profited equally from improved strategies. We sought to analyze sex-specific temporal trends in intensive care unit (ICU) admission and mortality in younger patients presenting with AMI or stroke in Switzerland. Methods Retrospective analysis of tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…Also in the group of burn patients, sex had no influence on ICU mortality [21]. On the contrary, there are more data regarding the reduced use of interventions and ICU resources for women with cardiovascular disease in comparison with men: women are less likely to receive a revascularization for cardiovascular disease also in Switzerland [2,22]. It has also been described that women are less likely to receive a tracheostomy [23], but this was not the case in our case series.…”
Section: Ventilationcontrasting
confidence: 56%
See 1 more Smart Citation
“…Also in the group of burn patients, sex had no influence on ICU mortality [21]. On the contrary, there are more data regarding the reduced use of interventions and ICU resources for women with cardiovascular disease in comparison with men: women are less likely to receive a revascularization for cardiovascular disease also in Switzerland [2,22]. It has also been described that women are less likely to receive a tracheostomy [23], but this was not the case in our case series.…”
Section: Ventilationcontrasting
confidence: 56%
“…While our group reported difference regardless of severity score in the use of invasive disease specific treatments for intracranial bleeding (women received less insertions of external ventricular drainage despite same size of the ventricles and same neurology) [30], no differences where observed in our institution regarding treatment for intracranial tumors and SAH [31,32]. The gender gap could have been narrowed thanks to guideline directed therapies [22].…”
Section: Ventilationmentioning
confidence: 61%
“…Over the last decade, gender medicine, encompassing both sex and gender, has increasingly gained interest in critical care research [ 5 , 6 ]. Recent research has aimed to investigate sex and gender differences in overall physiology, disease pathogenesis, provision of ICU resources, and outcomes [ 3 , 7 , 8 ]. Biological differences within the immune response and its modification by sex steroids have been discussed as a potential contributor to the increased susceptibility to infection and sepsis described in men [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, sex and gender differences in diagnosis, clinical care, and outcomes have become an increasing concern in medicine and critical care research [ 1 , 2 ]. Inequalities in medical care were first described via several landmark publications in the early 1990s which revealed that women often received inequitable treatment compared to men, often resulting in worse outcomes.…”
Section: Introductionmentioning
confidence: 99%